Implementation of the Independent Learning Curriculum in Improving Student Learning Outcomes - Lailawati Lailawati; Najmuddin Najmuddin; Siraj Siraj (Jurnal Inovasi Pendidikan dan Sains, 2025)
This study aims to describe and analyze the implementation of the Independent Learning Curriculum with a focus on the development of the school operational curriculum, the use of teaching tools, the Pancasila Student Profile (P5) project, and learning practices based on students’ learning stages to improve the quality of education. The research employed a qualitative descriptive method. Informants consisted of the school principal, vice principal, curriculum representatives, teachers, and driving teachers. Data were collected through interviews, observations, and documentation, and analyzed descriptively. The results show that the Independent Learning Curriculum is reflected in the integration of P5 across various fields, including religious devotion, mutual cooperation, and independent and creative learning. Differentiated learning is implemented by first mapping students’ needs through diagnostic assessments, designing learning modules, applying process differentiation strategies, and conducting continuous evaluation through formative and summative assessments. The implementation has contributed to improving the quality of education by enhancing the principal’s performance in aligning the School Operational Curriculum with national guidelines, strengthening teachers’ creativity in using media, technology, and teaching materials, and increasing students’ learning achievements. In conclusion, the Independent Learning Curriculum fosters innovation and collaboration that positively impact school performance and student competence